Monitoring occupational and environmental health as part of the right to the highest attainable standard of health - Chitsa, Ndakapara (Department of Public Health and Family Medicine, 2023)
Background: Environmental and Occupational Health (EOH) is a major contributor to global Burden of Diseases (BoD). State Parties (SPs) to the International Covenant on Economic, Social and Cultural Rights (ICESCR) are obligated to implement the Right to Health (RtH); which includes improving environmental and industrial hygiene, prevention, treatment and control of epidemic and occupational disease etc. Research shows that Noncommunicable diseases (NCDs) owing to EOH, and associated risk factors are the leading cause of death globally. Yet, ICESCR has a Committee on Economic, Social and Cultural Rights (CESCR) responsible for monitoring the implementation of the RtH. Also, Civil Society Organizations (CSO)'s role, acting as watchdogs, is to ensure that SPs comply with their obligation to realise the RtH. So far, little is known whether SPs, CESCR and CSOs are paying attention to EOH factors as one of conditions necessary for the realisation of the RtH. The purpose of this study is to investigate whether and how attention is given to EOH issues in implementing the RtH Methods: A mixed method study design was used for this study. From State Parties (SPs) to the Convention, stratified random sampling was used to select 3 countries per each World Health Organisation (WHO) epidemiological region (N=18). For each country, we collected State Party (SP) reports, Concluding Observations (CO), and CSO reports published on UN OHCHR website between 2009 and 2018. Data was analysed using word frequency and thematic analysis for SPs (n=21), COs (n=18) and CSOs (n=22) reports, in total 61 reports. Results: The attention given to EOH issues is limited. Where EOH factors were given attention, either the CESCR failed to adequately acknowledge their importance in the realisation of the RtH leading to the SPs reducing their focus and failing to report on EOH issues in their follow-up reports. Alternatively, the SP and CESCR did not follow through on issues previously raised leaving these concerns unaddressed. SPs appear to have no one to hold them accountable for RtH rights since neither CSOs nor the CSECR were effectively doing so. Conclusions: Addressing EOH health risks is required of governments to protect, fulfil, and respect the RtH. In this study, a minority of SPs addressed EOH. In addition, those who addressed EOH have largely focused on addressing consequences of rather than preventing the EOH burden. There is an urgent need for governments to address the root causes of failure to provide the conditions necessary for realisation of RtH – and specifically EOH factors - within the UN system. Further work needs to be done by the CESCR in strict monitoring of SPs' obligations in terms of EOH factors as described in its General Comment 14 (GC 14).